2018
DOI: 10.5812/compreped.62661
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Self-Care on Glycated Hemoglobin and Fasting Blood Sugar Levels on Adolescents with Diabetes

Abstract: Background: Type 1 diabetes is a chronic condition that causes many problems for adolescents and their families. Given the increasing prevalence of diabetes and the numerous complications of the disease that require long-term treatment and the need for daily blood glucose control, lifestyle modification and knowledge acquisition regarding self-care behaviors are essential throughout life. Objectives: Considering the increasing prevalence of diabetes, this study evaluated the effect of self-care education on gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The major feature of home phototherapy is the lack of mother-infant separation (14). Neonatal and child health in adulthood is important (15)(16)(17). Phototherapy at home can be a proper substitute for hospital interventions if the parents are educated about home phototherapy it is done under the supervision of trained nurses.…”
Section: Introductionmentioning
confidence: 99%
“…The major feature of home phototherapy is the lack of mother-infant separation (14). Neonatal and child health in adulthood is important (15)(16)(17). Phototherapy at home can be a proper substitute for hospital interventions if the parents are educated about home phototherapy it is done under the supervision of trained nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Triage nurses should be able to make appropriate decisions in a relatively short time, usually in a unknown and emotional situation (10). Nurses are one of the most important health care provider groups for children (17)(18)(19)(20)(21)(22)(23). Studies revealed several barriers to accurate triage, specially for children (24).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the proposed nutrition program resulted in a remarkable decrease of about 0.3 to 1.03 in the patients' HbA 1c . HbA 1c has been reported to drop as a result of other interventions including self-care intervention (Kazeminezhad et al, 2018) and medical nutrition therapy (Pastors et al, 2002).…”
Section: Discussionmentioning
confidence: 99%